2015
DOI: 10.1097/htr.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Postconcussion Symptoms on the Neurobehavioral Symptom Inventory

Abstract: These findings extend the findings of Meterko et al to other samples. Because findings were consistent across sample and subsamples, the current findings are applicable to both Department of Veteran Affairs and Department of Defense postdeployment medical evaluation settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 35 publications
(30 reference statements)
6
64
1
Order By: Relevance
“…In particular, we demonstrated that factors within the higher-order model have limited discriminant validity. The high correlation of factors in this model, consistent with other work (Joyce et al, 2015; Potter et al, 2006; Sady et al, 2014; Vanderploeg et al, 2015), suggests that researchers should avoid statistically forcing lower-order factors to be uncorrelated (i.e., through orthogonal rotation), as it parses symptoms that are highly coherent and thus properly represented by correlated dimensions (as in the higher-order model of our study) or a broad common factor (as in the bifactor model we presented). In contrast to a bifactor model, these types of models may mask the importance/dominance of a single, broad dimension accounting for large proportions of variance in the domain.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, we demonstrated that factors within the higher-order model have limited discriminant validity. The high correlation of factors in this model, consistent with other work (Joyce et al, 2015; Potter et al, 2006; Sady et al, 2014; Vanderploeg et al, 2015), suggests that researchers should avoid statistically forcing lower-order factors to be uncorrelated (i.e., through orthogonal rotation), as it parses symptoms that are highly coherent and thus properly represented by correlated dimensions (as in the higher-order model of our study) or a broad common factor (as in the bifactor model we presented). In contrast to a bifactor model, these types of models may mask the importance/dominance of a single, broad dimension accounting for large proportions of variance in the domain.…”
Section: Discussionsupporting
confidence: 92%
“…4 Summing these ratings yielded a global PCS score (PCS-8) ranging from 0 to 32. Because persistent PCS affect multiple neurobehavioral domains (i.e., vestibular, somatic/ sensory, cognitive, and emotional), 2 we also calculated two alternative PCS measures: a ''physical'' PCS score and a ''cognitive/ emotional'' PCS score. The physical PCS score (PCS-5; range = 0-20) included vestibular and somatic/sensory PCS items: balance problems or dizziness, sensitivity to noise, sensitivity to light, memory problems, and headaches.…”
Section: Army Starrs Cohortmentioning
confidence: 99%
“…1 TBI is also a risk factor for adverse consequences in various other neurobehavioral functions including vestibular, somatic/sensory, cognitive, and emotional. 2 Indeed, a subset of individuals can experience persistent physical, cognitive, and emotional post-concussive symptoms (PCS) after single or multiple TBI. 3,4 Numerous epidemiological studies have investigated prognostic factors and adverse consequences of persistent PCS.…”
Section: Introductionmentioning
confidence: 99%
“…The NSI total score represents the sum of severity ratings of 22 symptoms, and cluster scores (i.e., vestibular, somatic, cognitive, and affective) were derived per Merterko et al (2012). Recently, Vanderploeg et al (2015) validated the 4-factor model in military TBI populations.…”
Section: Participants and Sample Characteristicsmentioning
confidence: 99%